The impact of training some of the physical abilities and their impact in achieving ran (800) m for those with mental handicap simple - Ali, Salman (Journal of Physical Education, 2010)
The research consist of five chapters, they are : 1. introduction , the research importance in granting the mentality handicaps the required importance in the social affairs , as well as he preparations of the right training programmes in order to achieve the bet results. 2. The mentality handicaps elements as well as some physical abilities and other similar visual studies . 3. The training programme , instruments , statistics , tests, as well as the training course used in the research . 4. The results of the physical training course tests and it’s analysis and discussions, using statistical analyzing methods. 5. The conclusions and recommendations by researcher